From developmental Ireland to migration nation: immigration and shifting rules of belonging in the Republic of Ireland - Fanning, Bryan (Economic & Social Studies, 2010)
This paper considers how post-1950s Irish developmentalism fostered the economic, social and political acceptance of large-scale immigration following EU enlargement in 2004. It argues that economic imperatives alone cannot account for the national interest case for largescale immigration that prevailed in 2004. It examines the ?rules of belonging? deemed to pertain to citizens and immigrants within the key policy documents of Irish developmental modernisation and recent key policy documents which address immigration and integration. Similar developmental expectations have been presented as applying to Irish and immigrants alike. Irish human capital expanded in a context where ongoing emigration came to be presented in terms of agency, choice and individual reflexivity. It again expanded considerably due to immigration. It is suggested that in the context of the current economic downturn that Ireland has become radically open to migration in both directions.
Keywords: Economic development; Immigration; Social change; Human capital